Process Analysis and Simulation in Chemical Engineering - Gil Chaves, Iván Darío; López, Javier Ricardo Guevara; García Zapata, José Luis; Leguizamón Robayo, Alexander; Rodríguez Niño, Gerardo (Springer International Publishing : Imprint: Springer, 2016)
This book offers a comprehensive coverage of process simulation and flowsheeting, useful for undergraduate students of Chemical Engineering and Process Engineering as theoretical and practical support in Process Design, Process Simulation, Process Engineering, Plant Design, and Process Control courses. The main concepts related to process simulation and application tools are presented and discussed in the framework of typical problems found in engineering design. The topics presented in the chapters are organized in an inductive way, starting from the more simplistic simulations up to some complex problems.